Tourism and natural hazards: river landform changes due to geohazards and its influence on the economic development of ecotourism in Sabah, Malaysia - Adi Jafar; Ramli Dollah; Nordin Sakke; Mohammad Tahir Mapa; Eko Prayitno Joko; Marsitah Mohd Radzi; Ubong Imang; Syahruddin Awang Ahmad; Andika Ab. Wahab; Jemmy Amanda Sipatau (MDPI, 2022)
Geohazards are often portrayed as a calamity that has a detrimental effect on humans and the environment. It is usually uncommon to consider geohazards in the opposite context. Therefore, this study examines the positive effects of an earthquake event centered in Ranau, Sabah, especially from the aspect of ecotourism development. A total of 27 homestay entrepreneurs in Kampung Melangkap were interviewed in this study. The raw data collected during the interview were conceptually and descriptively analyzed using the ATLAS.ti 8 software. Observation techniques were used to supplement the interviews. This study found that the morphological changes of the Panataran Kedamaian River in Kampung Melangkap were a result of an earthquake centered in Ranau. This disaster has led to the development of more interesting physical attractions, attracting many tourists to Melangkap Village. The dramatic increase of tourists in Melangkap during the post-geohazard phase has become the starting point for the economic growth of ecotourism in the region. This is shown by the increase in the number of homestay entrepreneurs, the expansion in the size of their businesses, higher overall income of homestay entrepreneurs, and better job opportunities for the local population.